Relation to Social Reality as An Expression of Existential Internal Conflicts - M. X , Dumarov (Miasto Przyszłości, 2023)
This article analyzes socio-psychological approaches to the views of scientific schools on the study of the perceptual aspects of the formation of the attitude of young people to social reality in the science of psychology.